Preserving Continuity of Cancer Therapy in Patients with Hematologic Malignancies and Chronic Subdural Hematomas: Comparative Outcomes of Middle Meningeal Artery Embolization and Surgery - Esteban Ramirez-Ferrer; Juan P. Zuluaga-Garcia; Maria A. Sierra; Danielle Hammond; Hagop M. Kantarjian; Jeffrey S. Weinberg; Chibawanye I. Ene; Shaan M. Raza; Frederick F. Lang; Peter T. Kan; Stephen R. Chen; Christopher C. Young (Cancers, 2026)
Background/Objective: Hematologic cancer patients are at high risk of developing chronic subdural hematomas (cSDH), and traditional treatment with surgery is potentially risky in this patient population, with associated coagulopathy and thrombocytopenia. Neurointerventional endovascular middle meningeal artery embolization (MMAE) is emerging as a novel minimally invasive treatment method for cSDH, and its efficacy and complication profile has not been evaluated in patients with hematologic cancers. Methods: We conducted a retrospective cohort study of adults with hematologic malignancies and cSDH between 2015 and 2025 and compared the efficacy and safety of treatment with MMAE versus open surgery. Variables were abstracted from the medical records. Primary outcomes were necessity for rescue treatment within 180 days after the index procedure and time to restart systemic cancer therapy among patients whose treatment was held due to subdural hematoma. Inverse probability of treatment weighting (IPTW) was applied using covariate-balancing propensity scores to address confounding by indication. Time-to-event outcomes were analyzed using weighted Cox proportional hazards models and Kaplan–Meier methods. Results: A total of 67 patients with hematologic malignancies and cSDH were included (37 treated with MMAE and 30 with surgical evacuation). After IPTW, baseline covariates were well balanced between groups. MMAE was associated with a significantly lower risk of requiring rescue treatment than surgery (HR, 0.19; 95% CI, 0.05–0.81). This association persisted after accounting for the competing risk of death (Fine–Gray subdistribution HR, 0.21; 95% CI, 0.06–0.77). Prolonged Activated Partial Thromboplastin Time was associated with a higher risk of requiring rescue treatment. The median time to resume systemic therapy was significantly shorter following MMAE (13.5 days; 95% CI, 9–26) than after surgery (27.0 days; 95% CI, 22–50) (p = 0.005). Conclusions: In patients with hematologic malignancies and symptomatic cSDH, MMAE was associated with fewer rescue interventions and earlier resumption of systemic therapy compared with surgical evacuation, suggesting that embolization may represent an effective and minimally invasive treatment strategy that preserves continuity of oncologic care in this high-risk population.